2015
DOI: 10.4049/jimmunol.1501198
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Protects Lungs from Cockroach Allergen–Induced Inflammation by Modulating Mesenchymal Stem Cells

Abstract: Exposure to cockroach allergen leads to allergic sensitization and increased risk of developing asthma. Aryl hydrocarbon receptor (AhR), a receptor for many common environmental contaminants, can sense not only environmental pollutants but also microbial insults. Mesenchymal stem cells (MSCs) are multipotent progenitor cells with the capacity to modulate immune responses. In this study, we investigated whether AhR can sense cockroach allergens and modulate allergen-induced lung inflammation through MSCs. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 82 publications
4
56
0
Order By: Relevance
“…27,28 Briefly, mice were sensitized by means of intratracheal inhalation of 20 µg of CRE (B46; GREER Laboratories, Lenoir, NC) per mouse in 50 µL of PBS after achievement of light anesthesia with isoflurane on days 1, 2, 3, and 14 and challenged on days 20 and 22 with the same amount of CRE. Control mice received PBS during the sensitization and challenge phases.…”
Section: Methodsmentioning
confidence: 99%
“…27,28 Briefly, mice were sensitized by means of intratracheal inhalation of 20 µg of CRE (B46; GREER Laboratories, Lenoir, NC) per mouse in 50 µL of PBS after achievement of light anesthesia with isoflurane on days 1, 2, 3, and 14 and challenged on days 20 and 22 with the same amount of CRE. Control mice received PBS during the sensitization and challenge phases.…”
Section: Methodsmentioning
confidence: 99%
“…These MMVVδ mice also produced lower serum titers of CRE-specific IgE and IgG1 than WT counterparts ( Figure 1G). Allergic airway inflammation involves Th2 responses in the lungs (32,33). We found that CRE-treated MMVVδ mice showed much lower concentrations of Th2 cytokines IL-4, IL-5, and IL-13 ( Figure 1H).…”
Section: Ox-camkii Regulates Cre-induced Lung Function and Inflammationmentioning
confidence: 87%
“…Importantly, our data suggest that MMVVδ protects against allergen-induced AHR and lung inflammation in either CRE-or HDM-induced mouse models of asthma. These allergen-induced mouse models of asthma, particularly the well-established CRE-induced mouse model of asthma in our laboratory (33,37), are relevant to patients with asthma and mimic those asthmatic patients who are allergic to CRE. CRE exposure and sensitization has been identified as one of the strongest risk factors associated with the development, severity, and morbidity of asthma (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations